2011
DOI: 10.1007/s12011-011-9007-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Age Using Trace Element Concentrations in Hair and the Support Vector Machine Method

Abstract: Trace element content in hair is affected by the age of the donor. Hair samples of subjects from four counties in China where people are known to have long lifespan ("longevity counties") were collected and the trace element content determined. Samples were subdivided into three age groups based on the age of the donors from whom these were taken: children (0-15 years); elderly (80-99 years); and centenarians (≥100 years). We compared the trace element content in hair of different age groups of subjects. Suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, certain essential elements, such as Mn, Se and Zn, are critical to the human metabolism and aging [ 8 , 9 ]. Lv et al reported that the higher Mn levels in the hair of centenarians were conducive to their long lifespan [ 10 ]. Besides, Se is associated with the prevention of some diseases such as cancer and Alzheimer's disease, and also has important impacts on longevity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, certain essential elements, such as Mn, Se and Zn, are critical to the human metabolism and aging [ 8 , 9 ]. Lv et al reported that the higher Mn levels in the hair of centenarians were conducive to their long lifespan [ 10 ]. Besides, Se is associated with the prevention of some diseases such as cancer and Alzheimer's disease, and also has important impacts on longevity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Mn is known as an anti-aging element [33]. Lv J et al reported that the higher concentration of Mn in the hair of centenarians was conducive to their long lifespan [44].…”
Section: Discussionmentioning
confidence: 99%
“… 2 Chemical elements in hair not only reflect chemical body pools but also reflect age-related changes in nutritional requirements and metabolic processes. 3 Children and adults had significant differences in elemental levels as found in a US population. 4 A study concerning a Sudanese population found different elemental levels across age groups.…”
Section: Introductionmentioning
confidence: 91%